(untitled) (Bangladesh Pharmaceutical Journal, 2019)
Field experiment was conducted in absence and presence of potash and gypsum fertilizers, to compare and investigate the quantity levels of heavy metals and nutrients in leafy vegetables with growth stage and plant species variations, respectively. Seeds of Spinacia oleracia (Spinach), Colocasia esculenta (Taro), Ipoma aquatica (Water spinach), Cucurbita maxima (Pumpkin leaves), Basella alba (Indian spinach), Amaranthus gangeticus (Red amaranth), Coccinia grandis (Ivy gourd), Corchorus olitorius (Jute leaves), Basella rubra (Malabar Spinach), Coriandum sativum (Coriander leaves), Amaranthus lividus (Amaranth) were sown in the experimental filed in Joypurhat district of Bangladesh. The quantity of heavy metals [cadmium (Cd), lead (Pb), nickel (Ni), and zinc (Zn)] and nutrients [sodium (Na), potassium (K) and calcium (Ca)] in vegetables were determined by atomic absorption spectrometer and flame photometer, after the microwave digestion of these vegetables with 70% concentrated HNO3. The quantities of heavy metals were increased with the age of the plant, but the increases were not linear. Moreover, the order of heavy metals level in different vegetables was Zn >Ni >Cd >Pb. The Hazard Quotient (HQ) for Zn, Ni, Cd and Pb were as 0.143, 0.085, 0.1029 and 0.806, respectively. The sequence of HQ for the heavy metals followed the decreasing order Pb >Zn >Cd >Ni. The HQ value for all the heavy metals, Zn, Cd Ni and Pb were less than 1, which is considered safe or indicates no adverse effect on human health. Bangladesh Pharmaceutical Journal 22(1): 56-67, 2019